2022
DOI: 10.1002/eji.202149677
|View full text |Cite
|
Sign up to set email alerts
|

IL‐13 in dermal type‐2 dendritic cell specialization: From function to therapeutic targeting

Abstract: Skin functions as a barrier protecting the host against physical, thermal, chemical changes as well as microbial insults. The skin is populated by several immune cell types that are crucial to host defense and to maintain self-tolerance as well as equilibrium with beneficial microbiota. Conventional dendritic cells (cDCs) are antigen-presenting cells that patrol the skin and all other nonlymphoid tissues for self or foreign antigens, and then migrate to draining lymph nodes to initiate T-cell responses. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 110 publications
(142 reference statements)
0
13
0
Order By: Relevance
“…Atopic dermatitis is a disease related to type 2 immunity activation in response to environmental stimuli (2). Both adaptive and innate immune systems are involved in Type 2 immunity (2,12). Indeed, in the innate immune system activation, it has been showed that key roles are played by Group 2 lymphoid cells (ILC2), mast cells, basophils, eosinophils, and macrophages activated by interleukin (IL)-4 and/or IL-13 (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Atopic dermatitis is a disease related to type 2 immunity activation in response to environmental stimuli (2). Both adaptive and innate immune systems are involved in Type 2 immunity (2,12). Indeed, in the innate immune system activation, it has been showed that key roles are played by Group 2 lymphoid cells (ILC2), mast cells, basophils, eosinophils, and macrophages activated by interleukin (IL)-4 and/or IL-13 (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Both adaptive and innate immune systems are involved in Type 2 immunity (2,12). Indeed, in the innate immune system activation, it has been showed that key roles are played by Group 2 lymphoid cells (ILC2), mast cells, basophils, eosinophils, and macrophages activated by interleukin (IL)-4 and/or IL-13 (12)(13)(14)(15). Furthermore, also keratinocyte is implicated in this mechanism by expressing an increased level of IL-25, IL-33, and thymic stromal lymphopoietin (TSLP) (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations